Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/bf02859929
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroacupuncture on the pain threshold and the NMDA R1 mRNA in DRG on neuropathic pain rats

Abstract: To observe the effect of multiple electroacupuncture (EA) on the pain threshold and the regulation of N-methyl-D-aspartate (NMDA) receptor in dorsal root ganglia (DRG) of neuropathic pain rats. Rats were prepared with a unilateral chronic constriction injury (CCI) to the sciatic nerve. EA was done in acupoints "Huan Tiao" and "Yang Ling Quan" for 30 min every day and the thermal thresholds were detected after EA at 3, 5, 7, 10, 14 days after operation. On day 14 after nerve injury, the in situ hybridization me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Similar to our findings, consecutive applications of EA for three days in a model of visceral hypersensitivity in mice did not develop tolerance to the analgesic treatment with electroacupuncture [42]. However, some studies have demonstrated the participation of opioid system in the antihyperalgesia of electroacupuncture promoted by the application through the administration of blockers of μ and δ opioid receptors [8, 16, 1921, 27, 31, 33, 36, 43]. Other studies also confirmed the action of β -endorphin as evidenced, an increase in plasma after application of electroacupuncture in the postoperative ovariectomy in female dogs [24] and rats [27].…”
Section: Resultssupporting
confidence: 85%
“…Similar to our findings, consecutive applications of EA for three days in a model of visceral hypersensitivity in mice did not develop tolerance to the analgesic treatment with electroacupuncture [42]. However, some studies have demonstrated the participation of opioid system in the antihyperalgesia of electroacupuncture promoted by the application through the administration of blockers of μ and δ opioid receptors [8, 16, 1921, 27, 31, 33, 36, 43]. Other studies also confirmed the action of β -endorphin as evidenced, an increase in plasma after application of electroacupuncture in the postoperative ovariectomy in female dogs [24] and rats [27].…”
Section: Resultssupporting
confidence: 85%
“…Several animal studies have shown that EA treatment can attenuate the hyperalgesia of neuropathic pain through the downregulation of NMDAR phosphorylation at the spinal cord level [ 63 66 ]. EA decreases in the expression level of the NR-2B subunit of the NMDAR in the dorsal horn [ 51 , 67 – 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies have also revealed that acupuncture causes a reduction in glycine inhibition [ 102 ] and an increase in the activity of the neurotrophin BDNF (causing neuron plasticity) [ 101 ], NMDA, AMPA, and metabotropic glutamate receptors in the postsynaptic neurons [ 103 ]. Acupuncture increases the levels of these neuropeptides, including opioids, serotonin, norepinephrine, and amino acids and reduces the levels of the local inflammatory cytokines and the expression of their receptors [ 59 , 63 ]. In a neuropathic pain rat model, repeated EA had a time-dependent cumulative analgesic effect; this might be associated with its modulatory effects on NK cells, as well as on splenic IL-2, β -Endorphin ( β -EP), and plasma IL-2, IL-1 β , interferon gamma (IFN- γ ), and transforming growth factor beta (TGF- β ) levels [ 104 ].…”
Section: Methodsmentioning
confidence: 99%